Serum plant sterols as surrogate markers of dietary compliance in familial dyslipidemias. Issue 3 (June 2015) - Mateo-Gallego, Rocío; Baila-Rueda, Lucía; Mouratidou, Theodora; De Castro-Orós, Isabel; Bea, Ana M.; Perez-Calahorra, Sofía; Cenarro, Ana; Moreno, Luis A.; Civeira, Fernando
Summary Background & aims A well-balanced diet is the first-line treatment in hyperlipidemia. The objective was to study the association between serum phytosterols and dietary patterns to use them as surrogate markers of dietary compliance in primary dyslipidemias. Methods 288 patients with primary hyperlipidemias (192 autosomal dominant hypercholesterolemia (ADH) and 96 familial combined hyperlipidemia (FCHL)) were included. Principal factor analysis identified 2 major dietary patterns using a 137-item food frequency questionnaire. "Vegetable & Fruits pattern" was characterized by higher intake of fruits, green beans, nuts, tomatoes, roasted or boiled potatoes, lettuce and chard and lower of processed baked goods, pizza and beer. "Western pattern" was positively characterized by hamburgers, pasta, sunflower oil, rice, chickpeas, whole milk, veal, red beans and negatively with white fish. Serum non-cholesterol sterols were determined by HPLC-MS/MS. Results Plant sterols to-total cholesterol (TC) levels were lower with a higher adherence to a "Vegetable & Fruits pattern" (P = 0.009), mainly in ADH subjects (R2 = 0.019). Their concentration was greater with higher compliance to "Western pattern" especially in FCHL (P = 0.014). Higher levels of synthesis markers-to-TC with a greater adherence to "Vegetable & Fruits pattern" were found (P = 0.001) (R2 = 0.033 and R2 = 0.109 in ADH and FCHL respectively). Conclusion In subjects with primary dislipidemia, dietary patterns associate with serum absorption and synthesis markers, but no with lipid concentrations. The influence of diet on non-cholesterol sterols levels is not powerful enough to use them as subrogate markers.